Four cases of alcoholic myopathy complicated by acute renal failure - Takebayashi, Yoshihiro; Hiraga, Seigo; Kurata, Kazuhisa; Satoh, Takeshi; Hida, Miho; Nagai, Hiroko (Journal of Japanese Society for Dialysis Therapy, 1992)
Four cases of alcoholic myopathy complicated by acute renal failure are presented. Case 1: A 37-year-old man was admitted for acute renal failure with disturbed consciousness after heavy drinking. Case 2: A 50-year-old man with chronic alcohol toxity was admitted for acute renal failure. Case 3: A 37-year-old man with alcohol toxity was admitted for multiple organ failure. Case 4: A 35-year-old man was admitted for acute renal failure with disturbed consciousness after heavy drinking. Treatment by hemodialysis was performed for all four patients with acute renal failure, and acute renal failure improved in all cases after hemodialysis.